Formulation of an ergonomic assessment model of work-related musculoskeletal symptoms (WMSS) in small scale gold mining and extraction in the Philippines - Custodio, Benette P. (College of Engineering, University of the Philippines Diliman, 2016)
The small scale mining has provided jobs for millions of people and sufficient revenue for the governments in developing nations.A situationer from the Philippine Department of Environment and Natural Resources reported an estimate of 20,000 to 25,000 small scale miners in the Philippines as of December 2009.In many countries,small mining activities centre on the production of gold,including the Philippines.As stated by the Institute for Labor Studies,health and safety issue is a major concern for countries with small scale mining.Work-related Musculoskeletal Disorder(WMSD) is identified as a significant and costly,health and safety problem for the mining industry.However,there is no data and statistics available regarding the prevalence of Work-related musculoskeletal disorders (WMSD) in small scale gold mining and extraction in the Philippines leading to the absence of screening and disease prevention programs.Thus,there is a need to develop an ergonomic assessment model to identify and measure the level of risk factors that are associated to the occurrence of Work-related Musculoskeletal Symptoms(WMSS) in the small scale gold mining and extraction in the Philippines and come up with recommendations to minimize exposure to the associated risk factors.Individual (personal) factors,physical demand,and psychosocial stressors are the risk factors that may independently contribute to WMSS.In addition,these may also interact,resulting to a higher or lower provability of WMSS than the sum of the effect of individual factors.Data were gathered from study sites of the Mineral Extraction with Responsibility and Sustainability(MINERS) Program PROJECT G,in four regions of the Philippines where small scale gold mining is prevalent:Abra,Benguet,Compostella Valley,and Agusan del Norte.From the data,body parts with the highest prevalence of WMSS in the upper body,middle body,and extremities are shoulders (59.68%),lower back (65.32%),and knees (32.26%),respectively.Estimated alcohol consumption was found to be correlated to lower back severity, with a positive correlation coefficient.In addition,years of experience in mining/extraction is correlated to knee frequency and severity, with a positive correlation coefficient.Vitality demand is correlated to lower back severity, knee frequency,and knee severity,also with a positive correlation coefficient.With the use of a rule learning system,RIPPER algorithm,for classification of the samples,interactions between risk factors associated to the presence of WMSS in small scale mining and extraction in the Philippines were identified.In addition,baseline exposure limits were established and policies and action for the rules were provided to minimize exposure to the associated risk factors.